Effect of smartphone apps on glycemic control in young patients with type 1 diabetes: A meta-analysis - Pi, Linhua; Shi, Xiajie; Wang, Zhen; Zhou, Zhiguang (Frontiers in Public Health, 2023)
Objectives Achieving glycemic control is a great challenge for young patients with type 1 diabetes (T1D), especially during the transition from childhood to adulthood. As various smartphone apps have been developed to improve glycemic control in T1D, we performed a meta-analysis of randomized controlled trials to assess the effect of smartphone apps on glycemic control in young patients with T1D. Methods We systematically searched PubMed, Embase, and the Cochrane Library for randomized controlled trials comparing combined usual care and smartphone app treatment to usual care alone. This meta-analysis is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. The primary outcomes were the weighted difference in means (WMD) of HbA1c change from baseline and the person-years incidence of mild hypoglycemia or severe hypoglycemia between intervention and control groups. We assessed pooled data by use of a random-effects model. Results Of 1,190 identified studies, nine were eligible and included in our analysis (N = 748 participants). Relative to the control, using smartphone apps yielded a non-significant reduction in glycated hemoglobin (HbA1c) (WMD = −0.26, 95% CI: −0.56 to 0.05; p = 0.10) and no increased frequency of mild hypoglycemia (WMD = 1.87, 95% CI: −1.52 to 5.27; p = 0.49) or severe hypoglycemia (WMD = −0.04, 95% CI: −0.35 to 0.27; p = 0.80). In further subgroup analysis, compared with the recording-style app group, the auxiliary-style app group exhibited a significant reduction in HbA1c (WMD = −0.83, 95% CI: −1.10 to −0.56, p < 0.001). Conclusion The current pooled data analysis did not reveal a significant reduction in HbA1c in young patients with T1D undergoing treatment with smartphone apps and usual care in combination. However, auxiliary-style apps with insulin or carbo calculators were beneficial in reducing HbA1c.